Participation in the Georgia Food for Health programme and CVD risk factors: a longitudinal observational study - Miranda Alonna Cook; Kathy Taylor; Tammy Reasoner; Sarah Moore; Katie Mooney; Cecilia Tran; Carli Barbo; Stacie Schmidt; Aryeh D Stein; Amy Webb Girard (Cambridge University Press, 2023)
Abstract Objective: To assess the relationship between programme attendance in a produce prescription (PRx) programme and changes in cardiovascular risk factors. Design: The Georgia Food for Health (GF4H) programme provided six monthly nutrition education sessions, six weekly cooking classes and weekly produce vouchers. Participants became programme graduates attending at least 4 of the 6 of both the weekly cooking classes and monthly education sessions. We used a longitudinal, single-arm approach to estimate the association between the number of monthly programme visits attended and changes in health indicators. Setting: GF4H was implemented in partnership with a large safety-net health system in Atlanta, GA. Participants: Three hundred thirty-one participants living with or at-risk of chronic disease and food insecurity were recruited from primary care clinics. Over three years, 282 participants graduated from the programme. Results: After adjusting for programme site, year, participant sex, age, race and ethnicity, Supplemental Nutrition Assistance Program participation and household size, we estimated that each additional programme visit attended beyond four visits was associated with a 0·06 kg/m2 reduction in BMI (95 % CI -0·12, -0·01; P = 0·02), a 0·37 inch reduction in waist circumference (95 % CI -0·48, -0·27; P < 0·001), a 1·01 mmHg reduction in systolic blood pressure (95 % CI -1·45, -0·57; P < 0·001) and a 0·43 mmHg reduction in diastolic blood pressure (95 % CI -0·69, -0·17; P = 0·001). Conclusions: Each additional cooking and nutrition education visit attended beyond the graduation threshold was associated with modest but significant improvements in CVD risk factors, suggesting that increased engagement in educational components of a PRx programme improves health outcomes.